2007
DOI: 10.1109/tvcg.2007.70601
|View full text |Cite
|
Sign up to set email alerts
|

Topological Landscapes: A Terrain Metaphor for Scientific Data

Abstract: Abstract-Scientific visualization and illustration tools are designed to help people understand the structure and complexity of scientific data with images that are as informative and intuitive as possible. In this context, the use of metaphors plays an important role, since they make complex information easily accessible by using commonly known concepts. In this paper we propose a new metaphor, called "Topological Landscapes," which facilitates understanding the topological structure of scalar functions. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
104
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(104 citation statements)
references
References 44 publications
0
104
0
Order By: Relevance
“…We extend this measure to compare subtrees of a contour tree. Contour trees provide an abstract representation of a scalar field and have been recently used to explore high dimensional data via a two-dimensional terrain representation called the topological landscape [17,30,45]. Since our symmetry detection is essentially based on the contour tree, it can be used to identify repeating patterns in any dimension.…”
Section: Contour Tree For Data Exploration and Visualizationmentioning
confidence: 99%
“…We extend this measure to compare subtrees of a contour tree. Contour trees provide an abstract representation of a scalar field and have been recently used to explore high dimensional data via a two-dimensional terrain representation called the topological landscape [17,30,45]. Since our symmetry detection is essentially based on the contour tree, it can be used to identify repeating patterns in any dimension.…”
Section: Contour Tree For Data Exploration and Visualizationmentioning
confidence: 99%
“…The contour tree is a powerful visualization tool for abstract data representations [34], contour extractions [35], [36], transfer function design [37], etc. A number of algorithms have been used to compute contour trees [36], [38], [4].…”
Section: Feature-based Visualizationmentioning
confidence: 99%
“…[39] and Weber et al [34] showed that a contour tree can be decomposed into branches and rebuilt by assembling the branches afterward. Each branch rooted at an interior node, other than the two ends of the branch, is a child branch.…”
Section: Reversed Simplification Sequence and Branchesmentioning
confidence: 99%
“…Furthermore, the use of icons has been proposed by Shinagawa et al (Shinagawa et al, 1991). As it is difficult to match the resulting graph drawing to the scalar field, the use of colors has been proposed to identify connected components (Carr et al, 2004;Weber et al, 2007b;Weber et al, 2007a). Furthermore, Weber et al suggested the metaphor of a topological landscape (Weber et al, 2007b).…”
Section: Related Workmentioning
confidence: 99%